Biodiesel production from waste cooking oil using nickel doped onto eggshell catalyst - Muhammad Farid Fitri, Kamaronzaman; Haniza, Kahar; Nazatulshima, Hassan; Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2020)
The performance of nickel doped onto calcined chicken eggshell (CES-Ni) catalyst was investigated to produce biodiesel using waste cooking oil via transesterification. Several parameters were varied in order to obtain the most optimum conditions to produce biodiesel using nickel doped onto eggshell catalyst, such as methanol to oil molar ratio, metal loading, and catalyst dosage. The optimum conditions were obtained and discussed in details in this study.